Expressions of Interleukin-4 and Interleukin-5 in Nodular Prurigo and Pruritic Papular Lesions - Ayu Wikan Sayekti; Ann Kautsaria Putri; Dwi Retno Adi Winarni; Satiti Retno Pudjiati (Folia Medica Indonesiana, 2024)
Highlights: 1. An examination of IL-4 and IL-5 expressions in nodular prurigo and pruritic papular eruption is crucial for enhancing the effectiveness of biological agent therapy, specifically for HIV/AIDS patients. 2. The findings offer evidence suggesting the possibility of IL-4 as a treatment target for individuals diagnosed with nodular prurigo, as well as IL-4 and IL-5 for those diagnosed with pruritic papular eruption.